2020
DOI: 10.21203/rs.3.rs-23525/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic Control on Biogeography and Functioning of Rare-Biosphere Propionate Syntrophs in Paddy Field Soils

Abstract: Background Global biogeochemical processes are not only gauged by dominant taxa of soil microbiome but also depend on the critical functions of “rare biosphere” members. Here we evaluated the biogeographical pattern of “rare biosphere” propionate-oxidizing syntrophs in 113 paddy soil samples collected across eastern China. Results The relative abundance, functioning capacity and growth potential of propionate-oxidizing syntrophs were analyzed to provide a panoramic view of syntroph biogeographical distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In one study on rice field soil, Syntrophbacter was the most active SPOB at 15°C, whereas at 30°C Pelotomaculum and Smithella were also involved in degradation of propionate (Gan et al 2012). A biogeographical study spanning temperature zones demonstrated a correlation between higher temperature and higher propionate degradation rates and higher relative abundance of SPOB (Jin et al 2021). In Arctic peat, syntrophic propionate oxidation has been identified as the rate-limiting step for methane production at temperatures below 7°C, whereas at higher temperatures the propionate pool is depleted at a higher rate (Tveit et al 2015).…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In one study on rice field soil, Syntrophbacter was the most active SPOB at 15°C, whereas at 30°C Pelotomaculum and Smithella were also involved in degradation of propionate (Gan et al 2012). A biogeographical study spanning temperature zones demonstrated a correlation between higher temperature and higher propionate degradation rates and higher relative abundance of SPOB (Jin et al 2021). In Arctic peat, syntrophic propionate oxidation has been identified as the rate-limiting step for methane production at temperatures below 7°C, whereas at higher temperatures the propionate pool is depleted at a higher rate (Tveit et al 2015).…”
Section: Temperaturementioning
confidence: 99%
“…As these oxidized sulfur species are energetically more favorable electron acceptors than CO 2 , methanogens will be outcompeted. In habitats with restricted availability of electron acceptors other than CO 2 , such as biogas reactors, rice fields, peatlands, and oil reservoirs, propionate will instead be converted to methane (Chen et al 2020;Jin et al 2021;Kaspar and Wuhrmann 1978;Schmidt et al 2016). In these methanogenic ecosystems, propionate degradation proceeds through a closely interlinked multispecies cooperation between syntrophic propionate-oxidizing bacteria (SPOB) and hydrogen (H 2 )/formate-and acetate-utilizing methanogens (Stams 1994) (Fig.…”
Section: Introduction: Propionate -A Key Intermediate In Anaerobic Degradationmentioning
confidence: 99%